2016
DOI: 10.1007/s12011-016-0765-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molybdenum Nanoparticles on Blood Cells, Liver Enzymes, and Sexual Hormones in Male Rats

Abstract: Despite an increasing surge in application of nanoparticles in industries, there is a serious lack of information concerning their impact on human health and the environment. The present study investigated effects of molybdenum nanoparticles (Mo NPs) injected intraperitoneally into Sprague-Dawley rats at different doses of Mo NPs (5, 10, and 15 mg/kg BW per day) during a period of 28 days. Hematological and biochemical parameters as well as sexual hormones and histopathological examinations of the liver and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
3
13
0
2
Order By: Relevance
“…According to recent publications, Mo NPs could induce cytotoxicity, genotoxicity, and oxidative stress in mouse skin fibroblast cells and show cytoprotective effects in MCF-7 and HT-1080 cells [11,12]. Also in our previous work we found that the Mo NPs induced a reduction in the serum levels of testosterone in male rats, and histopathology of testis and liver showed a decrease in number of Leydig cells and an increase in chronic inflammatory cells respectively [13]. The aim of this study was to investigate the effect of MoO3 NPs exposure on serum levels of thyroid hormones in female rats.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…According to recent publications, Mo NPs could induce cytotoxicity, genotoxicity, and oxidative stress in mouse skin fibroblast cells and show cytoprotective effects in MCF-7 and HT-1080 cells [11,12]. Also in our previous work we found that the Mo NPs induced a reduction in the serum levels of testosterone in male rats, and histopathology of testis and liver showed a decrease in number of Leydig cells and an increase in chronic inflammatory cells respectively [13]. The aim of this study was to investigate the effect of MoO3 NPs exposure on serum levels of thyroid hormones in female rats.…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, it has been reported that Mo NPs significantly protect these and ZnO NPs In our previous study, our in vivo results, suggest that Mo NPs are toxic effect on serum levels of testosterone, AST, and LDH. However, there seemed to be no significant impact on the serum LH levels and hematological parameters [13]. Nano structures can move from body's entry portals into the circulatory and lymphatic systems, and finally into tissues and organs because of their very small sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of nanoparticles was assessed using the CCK-8 kit. After 24-h incubation, no cytotoxic effect was IJOMEH 2020;33 1Asadi et al [69] investigated the influence of MoNPs (no physicochemical characteristics of the nanoparticles was provided) on male Sprague-Dawley rats. The NPs were administered intraperitoneally in three concentrations: 5, 10 and 15 mg/kg daily for 28 days.…”
Section: Studies Showing Negligible or No Cytotoxicity Of The Nanoparmentioning
confidence: 99%
“…When Mo enters organisms, it can make up several Mo-enzymes such as aldehyde oxidase (AO), xanthine oxidase (XO), sulfite oxidase (SO), and nitrate reductase (NR). These Mo-enzymes are involved in various biochemical reactions through combining with respective substrates and play important roles in physiology 29 - 33 . In recent years, some metal alloys containing Mo such as Co-Cr-Mo have been found to possess excellent mechanical properties and good biocompatibility, and have been widely used as orthopedic and dental implants 34 - 36 .…”
Section: Introductionmentioning
confidence: 99%